Acquiring, Preserving, and Exhibiting a Comprehensive Collection of Vocal Music Recordings from Early- to Mid-Twentieth Century - Guise, Janneka; Martin, Bryan; Mason, James; Shaw, Rebecca (CAML Review / Revue de l'ACBM, 2020)
The Stratton-Clarke collection consists of approximately 200 linear feet of 78 and 33 1/3 rpm records, and thousands of digitized recordings that represents a comprehensive history of early twentieth century recorded Western sound, specifically opera -- its artists, roles, and early legacy from 78 rpm to early long play records. Along with someephemera and several pieces of historic playback equipment, a large financial gift will offset the costs of processing, preserving and providing access to the various formats represented in the collection. As the largest music research collection in Canada, the University of Toronto Music Library is fortunate to have the capacity to manage a donation of this magnitude. Each of our four authors has an important role to play to make the project a success. In this article we present a history and background of John Stratton, Stephen Clarke, and the collection itself, and document the many facets of a library taking on a donation of this size: donor relations and collaboration with the University’s advancement team and other stakeholders; the project management involved in making space and designing workflow for cataloguing, processing, and storage; archival description of the 78s and ephemera; preservation of the digital objects and digitization strategies for the analog recordings; the challenges and opportunities of working with large financial gifts; teamwork and managing students; and future plans for physical and online exhibitions of the collection.